Implementasi Kurikulum Pendidikan dalam Menghadapi Masalah Kualitas Pembelajaran - Nur Afiqoh Aprilia; Hadiyanto Hadiyanto; Yantoro Yantoro; Eka Sastrawati (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research is motivated by the low quality of learning in various educational units, one of the causes of which is the gap between curriculum design and classroom implementation. A good curriculum will not have a significant impact without effective implementation by teachers. Therefore, curriculum implementation plays a strategic role as a link between macro-level education policies and classroom learning practices. This study aims to analyze the impact of curriculum implementation on learning quality, identify supporting and inhibiting factors, and formulate strategies to strengthen learning quality. The method used is descriptive qualitative, using observation, interviews, and documentation techniques with teachers, principals, and elementary school students. The results show that the implementation of a flexible curriculum, such as the Independent Curriculum, encourages a shift from teacher-centered to student-centered learning, which increases student motivation and engagement through project-based learning and authentic assessment. However, teacher preparedness, limited infrastructure, and administrative burdens remain major obstacles. Authentic assessment has been shown to improve students' critical thinking skills and creativity, but requires consistent managerial support. The implication is that improving the quality of learning must be accompanied by strengthening teacher competency, the availability of resources, and adaptive school management so that curriculum transformation has a real impact on the quality of national education